Antibiosis and antixenosis resistance to oviposition by Bemisia tabaci (Gennadius) B biotype (Hemiptera: Aleyrodidae) in soybean genotypes - Horas,Vanusa Rodrigues (2018)
ABSTRACT: This study was aimed at assessing some biological parameters of Bemisia tabaci B biotype at immature stages to examine antibiosis in six soybean genotypes, besides antixenosis resistance to oviposition in choice and non-choice tests, under greenhouse and laboratory conditions. Between April 2016 and August 2016, bioassays were carried out at the Laboratory of Applied Entomology at College of Agricultural Sciences at Federal University of Grande Dourados (UFGD) Dourados (MS), Brazil. The following variables were evaluated: egg incubation period, nymphal and egg-to-adult duration, egg and nymph viability, and egg-to-adult survival on the soybean genotypes 68i70 RSF IPRO, M6210 IPRO, MS 947 IPRO, BMX Potência RR, M6410 IPRO, and ANTA 82 RR. Antixenosis resistance to oviposition by the silverleaf whitefly was found for MS 947 IPRO, while oviposition was highest for ANTA 82 RR, M6210 IPRO, and M6410 IPRO. The genotype MS 947 IPRO adversely affected egg and nymph viability, and egg-to-adult survival rates was the lowest among genotypes (59.75%), suggesting antibiosis resistance to this pest.